Gambaran Kejadian Efek Samping Kemoterapi Pasien Kanker Payudara Yang Menggunakan M-Health App “Pantau Kanker” Di Rumah Sakit Kota Yogyakarta - Nur P, Kanindya; Zukhruf Saputri, Ginanjar; Supadmi, Woro; Akrom, Akrom; Muhlis, Muh (JURNAL FARMASI GALENIKA, 2024)
Breast cancer is a type of cancer with a fairly high death rate. DIY Province has the highest prevalence of breast cancer in Indonesia. One of the medical ways to treat cancer is chemotherapy which uses cytostatic drugs, aimed at killing or slowing the growth of cancer cells. However, these drugs cause side effects in patients. Education is needed in dealing with side effects in order to monitor the patient's condition. Therefore, this research was conducted to determine the incidence of side effects of chemotherapy in breast cancer patients who use the M-Health app "Pantau Kanker" at Yogyakarta General Hospital. The research method used descriptive observational, with 41 patients as respondents. Recruitment was carried out using informed consent based on inclusion and exclusion criteria. Data collection was carried out using CRF (case report form) monitoring drug side effects. Data collection was carried out on the first, third and fifth days after chemotherapy. Monitoring is carried out through direct interviews with patients and through searching medical record data. Monitoring for nausea, vomiting and pain is carried out using the "Pantau Kanker" application based on the M-Health app with the VAS (visual analogue scale).  The results of this study showed that nausea often occurs on the first day, due to immediate side effects (24 hour duration). Then, those including delayed ADRs such as anorexia, insomnia are often found on the third day, while on the fifth day the majority occur alopecia and tingling pain. Some side effects, such as diarrhea, constipation, stomatitis (mouth ulcers), and fever, are not experienced by many patients. Some side effects, such as diarrhea, constipation, stomatitis (mouth ulcers), and fever are not experienced by many patients. The therapy regimen used is dominated by low emetogenic, so that the majority of side effects that appear are in the mild category and do not interfere with the patient's activities. The conclusion of the study shows that monitoring of side effects when using cytostatic drugs occurs between days 1 to 5, the majority are in the mild category so that the patient's daily activities can still run well.